Living the Spirit-led life: For all who are led by the Spirit of God are children of God. Romans 8:14 - Keefauver, Larry (U.S.A, 1997)
These 30 daily devotionals are written especially for Spirit-filled Christians, going through the Bible to show how the Holy Spirit can have a more powerful presence in life. Volume 2 focuses on the practice of the Spirit-led life.
Keywords: Holy Spirit -- Prayers and devotions